2022
DOI: 10.3389/fnut.2022.1006517
|View full text |Cite
|
Sign up to set email alerts
|

Multiomic analysis of dark tea extract on glycolipid metabolic disorders in db/db mice

Abstract: Glycolipid metabolic disorder is a serious threat to human health. Dark tea is a kind of traditional Chinese tea, which may regulate the glycolipid metabolic disorders. Dark tea extract (DTE) is the water extraction obtained from dark tea. Compared with traditional dark tea, DTE has the benefits of convenient consumption and greater potential for promoting health. However, the regulation of DTE on glycolipid metabolism and its molecular mechanism is rarely investigated. In our study, DTE was used as raw materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Statistics show that each year, almost 2.8 million individuals pass away due to obesity‐related illnesses (Wiciński et al, 2020 ), making the need for obesity treatment and prevention urgent. According to several researches, drinking dark tea may help prevent and cure obesity (Lim et al, 2022 ; Wang, Hu, et al, 2022 ). There have been claims that the dark tea variety TT offers anti‐obesity properties (Yuan et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Statistics show that each year, almost 2.8 million individuals pass away due to obesity‐related illnesses (Wiciński et al, 2020 ), making the need for obesity treatment and prevention urgent. According to several researches, drinking dark tea may help prevent and cure obesity (Lim et al, 2022 ; Wang, Hu, et al, 2022 ). There have been claims that the dark tea variety TT offers anti‐obesity properties (Yuan et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the BZBS-activated PPAR signaling pathway, genes such as Cyp4a32 , Cyp4a31 , Cyp4a14 , Cyp4a10 , and Plin4 were upregulated (Fig. 5 E), and these genes are involved in the regulation of glucose and lipid metabolism in db/db diabetic mice [ 49 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…53 In the process of QZT fermentation, GA content also showed a decreasing trend due to similar reasons, and the degradation of GA may be an important reason for the unique aging flavor of QZT. In addition, Feng et al isolated 3-O-methylgallate (62), salicyluric acid (63), xanthurenic acid (64), niacin (65), adipic acid (66), 4-hydroxycinnamic acid (67), quinic acid (68), coumarin (69), salicylic acid (70), coumaric acid (71), 2,5-dihydroxybenzaldehyde (72), 4hydroxybenzoic acid (73), 3-hydroxycoumarin (74), 2-(acetyloxy)-benzoic acid (75), salicylaldehyde (76), caffeic acid (77), indoleacrylic acid (78), theogallin (79), and other metabolic compounds (Figure 6). 44 Cheng et al also found five other phenolic acid compounds from QZT, including 3,5-diOH-benzoic acid (80), m-coumaric acid (81), 5-G-quinic acid (82), 3-p-coumaroyl-quinic acid (83), and α-linolenic acid (84).…”
Section: Flavonoids and Theirmentioning
confidence: 99%
“…74 Meanwhile, QZT can effectively increase the insulin cells in pancreatic tissue and reduce the blood sugar level to regulate diabetes and a series of complications. Wang et al investigated the influence of the extract from QZT on diabetic mice 75 and found that the QZT extract reduced the blood sugar level of diabetic mice, which further repaired the damage of pancreatic organs and stimulated insulin secretion, thus, relieving diabetes-related symptoms. In another study, Feng et al studied the inhibitory effects of changes to metabolites on lipase and α-amylase during the pile-fermentation of QZT.…”
Section: Health Benefits Of Qztmentioning
confidence: 99%